Micro-economics Practice Made Perfect Workbook - Normala Ismail (2024)
This MICROECONOMICS Practice Made Perfect Workbook is provided as a convenience to new students who have little or no understanding of basic microeconomic theories. This workbook is written and complied neatly according to the latest Principle of Economics and Microeconomics Course syllabus content for diploma students from various fields especially those studied in Universiti Teknologi MARA. All microeconomic concepts and exercises in this workbook is simplified by the author in accordance with thestudents’ level of understanding and learning. This workbook contains questions that challenge the minds of the students. Answers to questions are provided at the end of each topic as a guideline for students to better understand and appreciate microeconomics.